Автоколебания в цепи с лазерно-дуговым разрядом как основа новых импульсных технологий - Бушма, А.И.; Жерносеков, А.М. (Технічна електродинаміка, 2012)
Current self-oscillation properties of laser-arc discharge in circuit with inertia feedback were been investigated. It is established that the change of inertia feedback loop can be obtained as close to the harmonic oscillations and relaxation oscillations. Recommendations for the use of self-oscillation modes in the development of new combined pulse technologies are given.